Public Faces of Sharī’ah in Contemporary Indonesia: Towards a National Madhhab - MB. Hooker; Tim Lindsey (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
The thesis of this article that all faces and expressions of shari'ah in Indonesia must be read together and that together they point to a debate about Islamic law that, while fragmented, might be said to be peculiar to Indonesia. Can they be made to amount to assonance or is dissonance the characteristic of this Madhhab Nasional Shari'ah Republik Indonesia? And if dissonance is the defining characteristic, is that necessarily a bad thing? We will suggest some answers to these questions in the conclusion to this article.DOI: 10.15408/sdi.v10i1.637